Development of a simulation model for a hollow fiber membrane N2-H2 separation system - Ismail, A. F.; Haron, S. (Penerbit UTM Press, 2000)
An interactive simulation model to assist the design process of a hollow fiber membrane for gas separation system has been developed. The model is capable of predicting the performance of a multistage hollow fiber membrane permeator, regardless of any operating conditions employed. It takes into account the effect of feed and permeates pressure drop to simulate the multistage membrane process that is more applicable to the gas separation system. Various types of data profile are able to be produced such as permeate flux and feed pressure profile along the hollow fiber length for each membrane module. The simulation model has been tested using data from the real separation system. The results revealed that the model has been successfully predicted the performance of the NTH2 mixtures separation using a commercial size multiple stage hollow fiber membrane permeator. The maximum error is generally not over than 5%. The established model provides a more convenient process in designing a multistage membrane permeator system.